A proposal for restructuring Descriptor 3 of the Marine Strategy Framework Directive (MSFD). (December 2016) - Probst, Wolfgang Nikolaus; Rau, Andrea; Oesterwind, Daniel
Abstract: In 2015 the EU Commission decided to review the structure of the criteria and indicators of the Marine Strategy Framework Directive (MSFD). This paper reviews some shortcomings of the current structure of Descriptor 3 (D3) addressing the status of exploited fish and shellfish stocks and suggests a more operational structure for D3. By reframing D3, the assessments of stock size and size distribution within the stock could be addressed within two distinct criteria. When relating status parameters, such as stock size and size structure to human pressures, the first criterion would assess fishing intensity while the second criterion would assess the selectivity pattern acting upon a fish stock. Within each criterion, the indicators would be embedded within an indicator framework and thereby assigned to predefined indicator types. Three different indicator frameworks were compared and analysed with regards to its operationality within D3, namely pressure-state ( p -S), pressure-state-response (PSR) and driver-pressure-state-impact-response (DPSIR) frameworks. P-S or DPSIR were found to be either incomplete in fulfilling the MSFD reporting requirements ( p -S) or too complicated to be implemented in the mid-term (DPSIR). PSR thus appears to provide the best compromise between operationality and MSFD requirements and could be applied to criteria within other descriptors to obtain a consistent indicator structure within the MSFD. Highlights: Descriptor 3 (D3) of the Marine Strategy Framework Directive (MSFD) should be revised All indicators should be embedded within an indicator framework Indicator frameworks will assign clear roles to each indicator within the MSFD Three types of indicator frameworks are compared for the application within D3. Pressure-state-response frameworks may be best suited for rapid implementation